Social Media Technologies Used for Education: An Empirical Study on TAM Model During the COVID-19 Pandemic - Alismaiel, Omar A.; Cifuentes-Faura, Javier; Al-Rahmi, Waleed Mugahed (Frontiers in Education, 2022)
The study's major goal was to figure out what factors impact university students' behavior and intentions to use social media to boost their academic performance during the COVID-19 Pandemic. Given the context-dependent nature of online learning, the Technology Acceptance Model (TAM) was adopted and supplemented with components largely relevant to harnessing social media for collaborative learning and engagement. Collaborative learning, student participation, and a social media mindset are just a few of the new features. The enlarged model was validated using empirical data from an online survey questionnaire filled by a sample of 409 Saudi Arabia higher education students, which assesses students' social media usage intentions and academic performance during the COVID-19 Pandemic. AMOS-SEM was used to analyze the model's various assumptions (Analysis of Moment Structures- Structural Equation Modeling). The findings revealed that: (1) utilizing social media for collaborative learning and student engagement has a direct positive impact on perceived usefulness, ease of use, and enjoyment; (2) perceived usefulness, ease of use, and enjoyment has a direct positive impact on attitude to use social media; and (3) the link between TAM characteristics "usefulness, ease of use, and pleasure" and behavior intention to use social media is mediated by attitude to use social media. (4) Students' attitudes and behavior intentions on social media have a direct positive influence on their academic performance during the COVID-19 Pandemic. Academics, higher education institutions, and educational technology application providers will benefit greatly from the conclusions of this study, both theoretically and practically.